Investigation of metabolic processes of alcohol yeast during the fermentation of buckwheat-corn wort - E. M. Serba; E. R. Kryuchkova; L. V. Rimareva; M. B. Overchenko; N. I. Ignatova; S. V. Pavlenko (Пищевые системы)
To expand the range of competitive alcoholic beverages with original organoleptic properties, it is promising to study the use of new types of plant raw materials in grain distillate technologies. The purpose of this work was to establish the influence of the characteristics of the composition of grain wort prepared with the joint use of an alternative raw material source — buck- wheat and corn, which is widely used in alcohol production, on the metabolic processes of the yeast Saccharomyces cerevisiae 985-T and alcoholic fermentation. The objects of the study were buckwheat and corn; enzyme preparations — sources of amylases, xylanases, β-glucanases and proteases; samples of grain wort, mash and mash distillates. The prospects of introducing mixed grain media prepared using non-traditional buckwheat raw materials into the technology of original alcoholic beverages are substantiated. It was shown that the use of buckwheat as a source of biocomplete protein, essential amino acids and minerals together with corn containing a high level of starch and a low level of non-starch polysaccharides contributed both to an increase in the yield of alcohol and a change in the quantitative content of secondary metabolites in the composition of volatile impurities. It was found that an increase in the concentration of soluble carbohydrates in the wort and a decrease in its viscosity by 15.5–40.3% occurred due to the inclusion of corn in the composition of the grain mixture, and the enrichment of the wort with nitrogen assimilated by yeast by 19.0–41.8% — as a result adding buckwheat. The optimal ratio of corn and buckwheat in the composition of the grain mixture (7:3) was selected, which made it possible to improve the biochemical and technological parameters of grain must, increase the efficiency of the vital processes of yeast and alcoholic fermentation, ensure an increase in the yield of alcohol by 1.8%, reduce the formation of side metabolites, especially higher alcohols, and change their composition in the direction of increasing the proportion of aldehydes and esters, which can have a positive effect on the organoleptic characteristics of the distillate.